The mural in the modern architectural space. Integration between painting and architecture in the former Ministry of Public Education of Peru - Baca García, Manuel (2024)
Combine painting and architecture is a principle that artists of the first half of the 20th century considered fundamental to their approach to a unitary project. This article analyzes the pictorial works, in connection with their environment, inside the former Peruvian Ministry of Public Education building made between 1951 and 1956 by the architect Enrique Seoane Ros. The objective is to know the type of link between these creations and the space that contains it. For this purpose, we have applied the historical-critical method based on publications and visits to the referred place. The conclusions are related to the idea that the murals are integrated into modern thought, under artistic-political convergences and influences of the Bauhaus ideology, Le Corbusier’s theories and what Siqueiros called “Integral Plastic”. Finally, we find that these paintings qualify their architectural environment as an intrinsic value that transforms spatial perception.